The chronology of the Neolithic in Northwest Africa - S. Si-Ammour (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers the chrono-cultural evolution in the Northwest Africa territories during the Neolithic period. A systematic chronology based on specialized literature on the chrono-cultural features of this period in the Sahara and the Maghreb was inferred. It covers the following three major Neolithic currents characteristic of the Neolithic period in Northwest Africa: the Saharan Sudanese Neolithic, the Neolithic of Capsian Tradition, and the Mediterranean Neolithic. These currents were studied using the data on cultural behaviors with some radiocarbon dates. The results obtained revealed the features of the evolution from the Neolithization process to the full establishment of the Neolithic economy of production, as well as, a possible continuity to a Final Neolithic phase that lasted longer in some regions despite other regions that transitioned to the Eneolithic and the Iron Age. It was concluded that the evolution path that determined the characteristics of the Early, Middle, Late, and Final Neolithic phases was almost the same in different territories of the northwestern part of the African continent.